Markers of communicable infections transfusion route: the case of the blood bank of the School of Microbiology of the University of Antioquia, 2015-2016 (2019)
This book aims to estimate the seroprevalence of markers of infection transmissible via transfusion and its associated factors in donors attending the blood bank of the School of Microbiology of the Universidad de Antioquia, since 2015 to 2016. Previous studies have limitations related to the fact that the population cannot be extrapolated to this research, given that they do not take into account the new infection markers that were included in 2014 for screening in blood banks; it means, they don’t make disaggregated analysis by subgroups of interest in sociodemographic and hematological terms. A descriptive cross-sectional study was conducted, in which the global seroprevalence of transmissible infections in the blood bank was estimated, as well as the specific prevalence of HIV, HTLV, VHB, VHC, T. pallidum, and T. cruzi. The overallseroprevalence of infections was 3.39%, which in epidemiological terms can be considered a low occurrence. Although, from transfusion medicine, it could be considered high, given that this proportion represents a high number of deferred donors and units of discarded blood, to which the implications that this figure has for the blood bank and its donor selection process could be added. This study has multiple advantages, such as working with population data, exposing the magnitude of the occurrence of infections that are not routinely included in the programs of active epidemiological surveillance in Colombia and identifyinggroups with the highest occurrence of infections. At the same time, it has advantages of descriptive studies such as: generating hypotheses, simultaneously studying several events and several exposure factors, allowing the investigation oflong-term infections or slow development, and guiding health planning and administration actions.